(untitled) (Swiss Medical Weekly, 2014)
Transcatheter (or percutaneous) renal denervation is a novel technique developed for the treatment of resistant hypertension. So far, only one randomised controlled trial has been published, which has shown a reduction of office blood pressure. The Swiss Society of Hypertension, the Swiss Society of Cardiology, The Swiss Society of Angiology and the Swiss Society of Interventional Radiology decided to establish recommendations to practicing physicians and specialists for good clinical practice. The eligibility of patients for trancatheter renal denervation needs (1.) confirmation of truly resistant hypertension, (2.) exclusion of secondary forms of hypertension, (3.) a multidisciplinary decision confirming the eligibility, (4.) facilities that guarantee procedural safety and (5.) a long-term follow-up of the patients, if possible in cooperation with a hypertension specialist. These steps are essential until long-term data on safety and efficacy are available.